A waterproof and corrosion-resistant cable sheath material and preparation method thereof
By using green tea and tea to extract zinc-shaped zinc oxide by using green tea and tea, and mixed with modified polycopic acid -1,4-butanol ester and high-density polyethylene HDPE has poor environmental stress cracking performance in the underwater cable sheath, which realizes the efficient waterproof, corrosion resistance and durability of the material.
Patent Information
- Application Number
- CN202411215785.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-02
AI Technical Summary
When existing high-density polyethylene (HDPE) is used in cable sheath, its environmental stress cracking resistance is poor, limiting its application in the field of underwater cable sheath and increasing repair costs.
By extracting green tea and tea with zinc acetate mixing nanocrite-shaped zinc oxide, and mixed with modified polymeric acid -1,4-butanol ester and high-density polyethylene, formation of granules to form a cable sheath Material. Modified Juji dilate-1,4-butanol ester introduces epoxy base groups by reacting with epoxy fatty acid methane reactions, which improves its compatibility with HDPE and nanopotic zinc oxide.
It improves the waterproofness, corrosion resistance and environmental stress -resistant cracking performance of the cable protective material, enhance the overall durability and anti -rushing toughness, and reduce the repair cost of underwater cable.
Smart Images

Figure CN118755180B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable sheaths, and in particular to a waterproof and corrosion-resistant cable sheath material and a preparation method thereof. Background Art
[0002] High-density polyethylene (HDPE) is a white powder or granular product. It is non-toxic, odorless, with a crystallinity of 80% to 90%, a softening point of 125 to 135°C, and an operating temperature of up to 100°C. Its hardness, tensile strength and creep are better than those of low-density polyethylene. It has good wear resistance, electrical insulation, toughness and cold resistance. It has good chemical stability. At room temperature, it is insoluble in any organic solvent and is resistant to corrosion by acids, alkalis and various salts. The film has low permeability to water vapor and air and low water absorption. It has poor aging resistance and is not as resistant to environmental stress cracking as low-density polyethylene. In particular, thermal oxidation will reduce its performance.
[0003] Due to its excellent waterproof, electrical insulation and processability, HDPE is widely used as a sheath material and is very suitable for the preparation of waterproof and chemically resistant cable sheaths. For example, the application document with publication number CN104479191A, entitled A waterproof and chemically resistant heating cable sheath material and its preparation method, discloses the use of raw materials such as high-density polyethylene to prepare sheath materials. However, in the above technical solution, due to the long non-polar straight chain, few side chains and high crystallinity of HDPE, its environmental stress cracking (ESCR) resistance is poor, which to a certain extent limits its application in the field of underwater cable sheaths. In addition, the repair cost of underwater cables is high. Therefore, when using HDPE for waterproof and corrosion-resistant cable sheaths, its long-term waterproofness and corrosion resistance must also be considered to improve the overall durability of the cable sheath, thereby ensuring the long-term performance of underwater cables and reducing repair costs.
[0004] Compared with other thermoplastic polyester polymers, poly(1,4-butylene adipate) can provide good water resistance, low temperature resistance, heat resistance and mechanical properties. A small amount of poly(1,4-butylene adipate) mixed with HDPE can help improve the overall toughness, making the base material more suitable for underwater and submarine cable sheath applications. However, its molecular structure and chain structure are quite different from those of HDPE, so mixing with HDPE will cause incompatibility and processing difficulties. In addition, the interfacial interaction between the two phases is weak, which will increase the brittleness of the material under low temperature conditions, resulting in a decrease in impact toughness. In order to improve toughness and reduce brittleness, more chemical components need to be introduced, and some solvents have a greater impact on the environment, generating a large number of harmful byproducts.
[0005] Therefore, it is necessary to provide a cable waterproof and corrosion-resistant sheath material and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention
[0006] In view of this, the present invention provides a cable waterproof and corrosion-resistant sheath material and a preparation method thereof, so as to achieve the purpose of improving the compatibility of poly(1,4-butylene adipate) and high-density polyethylene while enhancing the waterproofness and corrosion resistance of the underwater cable sheath material, thereby improving the overall durability of the underwater cable.
[0007] To achieve the above object, the present invention provides a method for preparing a waterproof and corrosion-resistant cable sheath material, comprising the following steps:
[0008] S1, adding zinc acetate to green tea extract to prepare nano-sheet zinc oxide;
[0009] S2, using 4-methylcyclohexanone solution and epoxy fatty acid methyl ester to modify poly (1,4-butylene adipate) to obtain modified poly (1,4-butylene adipate);
[0010] S3, mixing high-density polyethylene and modified poly(1,4-butylene adipate) with nano-flaky zinc oxide, and extruding and granulating to obtain a cable sheath material.
[0011] The present invention optimizes the structure of nano ZnO. The spherical structure of nano zinc oxide in the prior art is difficult to form a dense protective layer, and is poor in dispersibility and interface compatibility. Therefore, more chemical components need to be added when preparing a waterproof and corrosion-resistant sheath material. Compared with the spherical structure of ZnO in the prior art, the nano sheet ZnO provided by the present invention can form a dense protective layer due to its high specific surface area, blocking the invasion of corrosive media, reducing the contact area between the corrosive media and the base material, reducing the corrosion rate, and improving the corrosion resistance of the base material. At the same time, the nano sheet ZnO also has good antibacterial properties. When it is dispersed in a base for underwater and undersea environments, it can work together with the dense base surface to exert its performance of resisting the attachment of aquatic bacteria, and indirectly improve the corrosion resistance.
[0012] In the present invention, epoxy fatty acid methyl ester reacts with the carboxyl group in poly(1,4-butylene adipate) to introduce epoxy groups, and the only byproduct in this process is water, which is more environmentally friendly than other epoxy monomers; and the epoxy groups can not only react with the carbon-carbon double bonds in HDPE, but also produce hydrogen bonds with nano-sheet ZnO, thereby improving the compatibility of epoxy-modified poly(1,4-butylene adipate) and nano-sheet ZnO in HDPE; at the same time, melt blending of epoxy-modified poly(1,4-butylene adipate) and HDPE can form a denser surface, reduce the probability of water penetration, improve the waterproofness of the matrix, give the matrix a certain effect of resisting water erosion, reduce the rough surface required for the growth of aquatic microorganisms, thereby reducing the possibility of biological attachment, thereby indirectly improving the corrosion resistance and long-term durability, and making the matrix more suitable for the application scenarios of underwater and undersea cable sheath materials; in addition, the denser surface also improves the flexibility of the matrix, reduces the risk of brittle fracture, and improves the ESCR (environmental stress cracking resistance) performance of the matrix.
[0013] The nano-sheet ZnO in the present invention also has excellent mechanical properties. When melt-blended with HDPE and poly(1,4-butylene adipate), hydrogen bonding occurs. In addition, the high rigidity of the nanoparticles themselves can effectively disperse external forces, improve the overall hardness, strength and wear resistance, thereby further improving the corrosion resistance. Moreover, compared with the spherical structure, the nano-sheet structure has a stronger interface effect with the matrix material, further enhancing the overall mechanical properties.
[0014] Optionally, the preparation of the nano-sheet zinc oxide includes mixing and stirring a green tea extract with zinc acetate to react, cooling to room temperature, centrifuging to obtain a precipitate containing nano-sheet zinc oxide, and drying and annealing the precipitate to obtain nano-sheet zinc oxide.
[0015] The present invention uses green tea extract and zinc acetate as raw materials. The green tea extract is rich in epigallocatechin gallate (EGCG). ECGC has reducing properties. Its hydroxyl group (-OH) and ester group (-COO-) can act as electron donors to react with zinc ions, promote the reduction of zinc ions to zinc atoms, and then react with oxygen in an alkaline environment to generate nano-sheet ZnO. In this process, the green tea extract is alkaline, and the carbonyl group (C=O) in ECGC has a strong attraction to zinc ions and has a certain affinity for zinc, which can react with Zn 2+ Forming a strong interaction, phenolic hydroxyl (-OH) can interact with Zn 2+The formation of coordination bonds and benzene ring structures can form π-π interactions with the ZnO surface or through electron donor-acceptor interactions. This coordination, interaction and alkaline solution environment are conducive to the nucleation and growth of ZnO nanoparticles, thereby forming nano-sheet ZnO. At the same time, ECGC also has a certain surface activity and can be adsorbed on the surface of newly formed nanoparticles to prevent agglomeration between particles and keep the particles uniformly dispersed during the formation process. The present invention uses an extract prepared from green tea leaves (containing catechins (EGCG)) as a reducing agent and stabilizer to prepare nano-sheet ZnO in a green and simple method, while reducing costs, it also provides a suitable solution environment for the induced formation of sheet structures.
[0016] Optionally, the mixing temperature is 60~80℃, and the time is 1~2h; the centrifugal speed is 5000~7000rpm; the drying condition is 80~90℃, and the time is 1.5~2.5h; the annealing condition is 190~210℃, and the time is 2~3h; the mass ratio of the green tea extract to zinc acetate is 45~50:5~7.
[0017] Annealing in the present invention helps to improve the crystal structure of the ZnO nanosheets, thereby improving its crystallinity, and also helps to remove internal stress and reduce defects, thereby improving the mechanical strength of the material and improving its overall performance.
[0018] Optionally, the preparation of the green tea extract includes removing impurities from the surface of the green tea leaves, crushing them after washing, adding ten times the weight of water and stirring at 70-80°C, filtering the filtrate using a non-woven filter material with an average pore size of about 20-25 μm, and storing at 4°C for later use.
[0019] Optionally, the preparation of the modified poly(1,4-butylene adipate) in S2 includes mixing 4-methylcyclohexanone solution, poly(1,4-butylene adipate) and epoxy fatty acid methyl ester for reflux reaction, then cooling to room temperature, adding excess ethanol, stirring and standing, filtering and drying to obtain a precipitate.
[0020] Optionally, the weight ratio of the 4-methylcyclohexanone solution, poly(1,4-butylene adipate) and epoxy fatty acid methyl ester is 100:4-6:8-12, and the mass ratio of the ethanol to poly(1,4-butylene adipate) is 4-6:400-450.
[0021] The addition of excessive ethanol in the present invention will increase the precipitation of the precipitate.
[0022] Optionally, the temperature of the reflux reaction in S2 is 70~80°C, and the reaction time is 20~2h; the stirring rate is 450~550r / min, and the stirring time is 1.5~2.5h; the standing time is 0.5~1h; and the drying is vacuum drying at 70~80°C for 3~4h.
[0023] Optionally, the filtration uses a vacuum filter, and the filtered solution is evaporated at a temperature of 50° C. and a vacuum degree of 0.1 bar, and the obtained condensed solution is a 4-methylcyclohexanone solution, which can be stored and reused.
[0024] The 4-methylcyclohexanone used in the present invention is environmentally friendly, less toxic than other solvents, decomposes quickly, and has less impact on aquatic organisms. It can also be recycled through low-temperature evaporation to achieve the effect of reducing costs.
[0025] Optionally, the S3 comprises the following raw materials in parts by weight: 91-95 parts of high-density polyethylene, 4-6 parts of modified poly(1,4-butylene adipate), and 1-3 parts of nano-flaky zinc oxide; the extrusion granulation conditions are a temperature of 180-200°C and a rotation speed of 300-380 r / min.
[0026] In order to achieve the above object, the present invention also provides a sheath material obtained by the above preparation method.
[0027] The sheath material obtained by the preparation method provided by the present invention does not need to introduce too much raw materials to adjust compatibility and other properties, and has excellent waterproof, corrosion-resistant, environmental stress cracking (ESCR)-resistant and impact toughness properties, thereby improving the overall durability of the underwater cable.
[0028] The above technical solution of the present invention includes at least the following beneficial effects:
[0029] The invention provides a method for preparing a waterproof and corrosion-resistant cable sheath material. The prepared nano-sheet ZnO is introduced to serve as a sacrificial anode to absorb corrosive media and protect the cable, and to form a dense protective layer to block the entry of corrosive media and improve the corrosion resistance and waterproofness of the sheath material. The modified poly(1,4-butylene adipate) is introduced into epoxy groups by reacting with epoxy fatty acid methyl ester, reacting with carbon-carbon double bonds in high-density polyethylene, and generating hydrogen bonds with the nano-sheet ZnO to improve the compatibility of the raw material system. At the same time, the formed sheath material has a denser surface, reduces the probability of water penetration, and thus improves the waterproofness and corrosion resistance. The modified poly(1,4-butylene adipate) also improves the flexibility of the sheath material, reduces the risk of brittle fracture, and thus improves the environmental stress cracking resistance of the sheath material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a 60-fold magnified electron microscope scanning image of the nano-sheet zinc oxide in Example 1 of the present invention;
[0031] Figure 2 This is an electron microscope scanning image magnified 60,000 times of the nano-sheet zinc oxide in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0033] Example 1
[0034] Preparation of corrosion-resistant nanoparticles:
[0035] The green tea leaves were thoroughly washed with tap water to remove soil and pollutants on their surface, then washed with deionized water for 3 times, dried at 80°C for 1h, and crushed into powder in a grinder. 50 parts of tea powder were added to 500 parts of deionized water, stirred at 80°C for 1h, cooled to room temperature, and the supernatant was filtered with a non-woven filter material with an average pore size of about 20μm to obtain a tea extract, which was stored at 4°C for subsequent use. 6 parts of zinc acetate were added to 50 parts of tea extract, and then stirred at 60°C for 2h to obtain a colloid. The color of the solution changed, indicating the formation of ZnO. It was cooled to room temperature, centrifuged at 6000rpm, and washed with deionized water 3 times to obtain a precipitate containing nano zinc oxide. The obtained precipitate was dried at 90°C for 2h, and the dried powder was annealed in a muffle furnace at 200°C for 3h to form nano-sheet zinc oxide, i.e., corrosion-resistant nanoparticles. The size of the prepared nanoparticles was between 50-60nm.
[0036] Preparation of waterproof and corrosion-resistant cable sheath materials:
[0037] Add 100 parts of 4-methylcyclohexanone solution, 6 parts of poly(1,4-butylene adipate) and 10 parts of epoxy fatty acid methyl ester to the reactor and reflux for 24 hours at 70°C. After the reaction is completed, cool the reaction mixture to room temperature, add 400 parts of ethanol, stir at 500r / min for 2 hours, make it evenly dispersed and stand for 1 hour, then place it in a vacuum filter to filter out the precipitate, wash the precipitate with a small amount of ethanol, and vacuum dry it at 70°C for 4 hours to obtain modified poly(1,4-butylene adipate). Pour the filtered solution into an evaporator, start evaporation at 50°C and a vacuum degree of 0.1 bar, collect the condensed 4-methylcyclohexanone solution, and store it in a dry, sealed container. HDPE and modified poly(1,4-butylene adipate) were dried in an oven at 80°C for 10 hours to eliminate absorbed moisture, and then 93 parts of HDPE, 6 parts of modified poly(1,4-butylene adipate) and 1 part of nano-flaky zinc oxide were mixed and added to a twin-screw extruder for extrusion at a processing temperature of 180°C and a screw speed of 300r / min. The extruded material was water-cooled and granulated to obtain a waterproof and corrosion-resistant cable sheath material.
[0038] Example 2
[0039] Preparation of corrosion-resistant nanoparticles:
[0040] The green tea leaves were thoroughly washed with tap water to remove soil and pollutants on their surface, then washed with deionized water three times, dried at 70°C for 1h, and crushed into powder in a grinder. 50 parts of tea powder were added to 500 parts of deionized water, stirred at 70°C for 2h, cooled to room temperature, and the supernatant was filtered with a non-woven filter material with an average pore size of about 25μm to obtain a tea extract, which was stored at 4°C for subsequent use. 5 parts of zinc acetate were added to 48 parts of tea extract, and then stirred at 80°C for 2h to obtain a colloid. The color of the solution changed, indicating the formation of ZnO. It was cooled to room temperature, centrifuged at 5000rpm, and washed with deionized water three times to obtain a precipitate containing nano zinc oxide. The obtained precipitate was dried at 80°C for 2.5h, and the dried powder was annealed in a muffle furnace at 190°C for 3h to form nano-sheet zinc oxide, i.e., corrosion-resistant nanoparticles. The size of the prepared nanoparticles was between 50-60nm.
[0041] Preparation of waterproof and corrosion-resistant cable sheath materials:
[0042] Add 100 parts of 4-methylcyclohexanone solution, 5 parts of poly(1,4-butylene adipate) and 12 parts of epoxy fatty acid methyl ester to the reactor and reflux for 20 hours at 80°C. After the reaction is completed, cool the reaction mixture to room temperature, add 420 parts of ethanol, stir at 450r / min for 2.5 hours, let it stand for 0.5 hours after it is evenly dispersed, and then place it in a vacuum filter to filter out the precipitate, wash the precipitate with a small amount of ethanol, and vacuum dry it at 80°C for 3 hours to obtain modified poly(1,4-butylene adipate). Pour the filtered solution into an evaporator, start evaporation at 50°C and a vacuum degree of 0.1 bar, collect the condensed 4-methylcyclohexanone solution, and store it in a dry, sealed container. HDPE and modified poly(1,4-butylene adipate) were dried in an oven at 80°C for 10 hours to eliminate absorbed moisture, and then 91 parts of HDPE, 6 parts of modified poly(1,4-butylene adipate) and 3 parts of nano-flaky zinc oxide were mixed and added to a twin-screw extruder for extrusion at a processing temperature of 180°C and a screw speed of 340r / min. The extruded material was water-cooled and pelletized to obtain a waterproof and corrosion-resistant cable sheath material.
[0043] Example 3
[0044] Preparation of corrosion-resistant nanoparticles:
[0045] The green tea leaves were thoroughly washed with tap water to remove soil and pollutants on their surface, then washed with deionized water for 3 times, dried at 75°C for 1h, and crushed into powder in a grinder. 50 parts of tea powder were added to 500 parts of deionized water, stirred at 75°C for 1.5h, cooled to room temperature, and the supernatant was filtered with a non-woven filter material with an average pore size of about 22μm to obtain a tea extract, which was stored at 4°C for subsequent use. 7 parts of zinc acetate were added to 49 parts of tea extract, and then stirred at 70°C for 2h to obtain a colloid. The color of the solution changed, indicating the formation of ZnO. It was cooled to room temperature, centrifuged at 7000rpm, and washed with deionized water to obtain a precipitate containing nano zinc oxide. The obtained precipitate was dried at 85°C for 1.5h, and the dried powder was annealed in a muffle furnace at 210°C for 2h to form nano-sheet zinc oxide, i.e., corrosion-resistant nanoparticles. The size of the prepared nanoparticles was between 50-60nm.
[0046] Preparation of waterproof and corrosion-resistant cable sheath materials:
[0047] Add 100 parts of 4-methylcyclohexanone solution, 5 parts of poly(1,4-butylene adipate) and 9 parts of epoxy fatty acid methyl ester to the reactor and reflux for 22 hours at 75°C. After the reaction is completed, cool the reaction mixture to room temperature, add 430 parts of ethanol, stir at 470r / min for 1.5 hours, make it evenly dispersed and stand for 1 hour, then place it in a vacuum filter to filter out the precipitate, wash the precipitate with a small amount of ethanol, and vacuum dry it at 75°C for 3.5 hours to obtain modified poly(1,4-butylene adipate). Pour the filtered solution into an evaporator, start evaporation at 50°C and a vacuum degree of 0.1 bar, collect the condensed 4-methylcyclohexanone solution, and store it in a dry, sealed container. HDPE and modified poly(1,4-butylene adipate) were dried in an oven at 80°C for 10 hours to eliminate absorbed moisture, and then 95 parts of HDPE, 4 parts of modified poly(1,4-butylene adipate) and 1 part of nano-flaky zinc oxide were mixed and added to a twin-screw extruder for extrusion at a processing temperature of 200°C and a screw speed of 380r / min. The extruded material was water-cooled and granulated to obtain a waterproof and corrosion-resistant cable sheath material.
[0048] Example 4
[0049] Preparation of corrosion-resistant nanoparticles:
[0050] The green tea leaves were thoroughly washed with tap water to remove soil and pollutants on their surface, then washed with deionized water for 3 times, dried at 75°C for 1h, and crushed into powder in a grinder. 50 parts of tea powder were added to 500 parts of deionized water, stirred at 78°C for 2h, cooled to room temperature, and the supernatant was filtered with a non-woven filter material with an average pore size of about 24μm to obtain a tea extract, which was stored at 4°C for subsequent use. 6 parts of zinc acetate were added to 47 parts of tea extract, and then stirred at 75°C for 2h to obtain a colloid. The color of the solution changed, indicating the formation of ZnO. It was cooled to room temperature, centrifuged at 6500rpm, and washed with deionized water to obtain a precipitate containing nano zinc oxide. The obtained precipitate was dried at 81°C for 2h, and the dried powder was annealed in a muffle furnace at 205°C for 1h to form nano-sheet zinc oxide, i.e., corrosion-resistant nanoparticles. The size of the prepared nanoparticles was between 50-60nm.
[0051] Preparation of waterproof and corrosion-resistant cable sheath materials:
[0052] Add 100 parts of 4-methylcyclohexanone solution, 4 parts of poly(1,4-butylene adipate) and 11 parts of epoxy fatty acid methyl ester to the reactor and reflux for 23 hours at 72°C. After the reaction is completed, cool the reaction mixture to room temperature, add 410 parts of ethanol, stir at 530r / min for 2 hours, make it evenly dispersed and stand for 1 hour, then place it in a vacuum filter to filter out the precipitate, wash the precipitate with a small amount of ethanol, and vacuum dry it at 73°C for 3 hours to obtain modified poly(1,4-butylene adipate). Pour the filtered solution into an evaporator, start evaporation at 50°C and a vacuum degree of 0.1 bar, collect the condensed 4-methylcyclohexanone solution, and store it in a dry, sealed container. HDPE and modified poly(1,4-butylene adipate) were dried in an oven at 73°C for 10 hours to eliminate absorbed moisture, and then 92 parts of HDPE, 6 parts of modified poly(1,4-butylene adipate) and 2 parts of nano-flaky zinc oxide were mixed and added to a twin-screw extruder for extrusion at a processing temperature of 200°C and a screw speed of 380r / min. The extruded material was water-cooled and pelletized to obtain a waterproof and corrosion-resistant cable sheath material.
[0053] Example 5
[0054] Compared with Example 1, the only difference is that the mass ratio of the green tea extract to zinc acetate is 45:7, and the other raw materials and steps are the same as those in Example 1.
[0055] Example 6
[0056] Compared with Example 2, the only difference is that the weight ratio of 4-methylcyclohexanone solution, poly(1,4-butylene adipate) and epoxy fatty acid methyl ester is 100:4:8, and the other raw materials and steps are consistent with Example 2.
[0057] Example 7
[0058] Compared with Example 3, the only difference is that 94 parts of high-density polyethylene, 4 parts of modified poly(1,4-butylene adipate), and 2 parts of nano-sheet zinc oxide are used, and the other raw materials and steps are the same as those in Example 2.
[0059] Comparative Example 1
[0060] Compared with Example 1, the only difference is that nano-platelet zinc oxide is not used.
[0061] Comparative Example 2
[0062] Compared with Example 1, the only difference is that commercially available zinc oxide is used instead of the prepared nano-sheet zinc oxide.
[0063] Comparative Example 3
[0064] Compared with Example 1, the only difference is that poly(1,4-butylene adipate) is used instead of modified poly(1,4-butylene adipate).
[0065] The nano-sheet particles prepared in Example 1 were scanned by electron microscope, and the Figure 1 , Figure 2 .
[0066] The performance of the sheath materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3 was tested, wherein the waterproof performance test method was derived from the electrical test method in GB / T 2951.13-2008, and the sample was judged to be qualified if it was not punctured; the winding performance and impact resistance test methods were derived from the sheath low-temperature winding test and sheath low-temperature impact test in GB / T 2951.14-2008, and the result evaluation method was that when the sheath samples were checked with normal vision or corrected vision without a magnifying glass, there should be no cracks in the sheath samples; the environmental stress cracking resistance test method was derived from the environmental stress cracking resistance test in GB / T 2951.41-2008, and the result evaluation method was that when the first crack appeared on the specimen during normal vision detection, the specimen failed, and the A step passed when no more than 5 failed specimens were present, and the B step passed when no failed specimens were present, and the conditions of the B step were more stringent; the corrosion resistance test method was derived from GB / T 10125-2021 neutral salt spray test, the result evaluation method is the appearance after the test.
[0067] Table 1 Performance test results of sheath materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3
[0068]
[0069] It can be seen from the results in Table 1 that the waterproof performance, corrosion resistance, winding performance, impact resistance and environmental stress cracking resistance of the sheath materials prepared in Examples 1 to 7 of the present invention are better than those of the sheath materials prepared in Comparative Examples 1 to 3, thereby improving the overall durability of the cable.
[0070] Combination Figure 1 , Figure 2 It can be seen that the overall structure of the nano-sheet zinc oxide prepared in Example 1 is sheet-like when magnified 60 times. After being magnified 60,000 times, it can be seen that the single particle of the nano-sheet zinc oxide is also a sheet-like structure, and the particle size is 50-60 nanometers.
[0071] Combining the performance of Example 1 and Comparative Examples 1-2 in Table 1, it can be seen that the waterproofness and environmental stress cracking resistance of Comparative Example 2 are better than those of Comparative Example 1, and the waterproofness, environmental stress cracking resistance, windability, impact resistance and corrosion resistance of Examples 1-7 are all better than those of Comparative Example 1, that is, the nano-sheet zinc oxide prepared by the present invention improves the waterproofness, windability, impact resistance, corrosion resistance and environmental stress cracking resistance of the sheath material.
[0072] Combining the performance of Example 1 and Comparative Example 3 in Table 1, it can be seen that the waterproofness, environmental stress cracking resistance, windability, impact resistance and corrosion resistance of Examples 1 to 7 are all better than those of Comparative Example 3, that is, the modified poly(1,4-butylene adipate) prepared by the present invention improves the waterproofness, windability, impact resistance, corrosion resistance and environmental stress cracking resistance of the sheath material.
[0073] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a waterproof and corrosion-resistant cable sheath material, characterized in that: The following steps are involved: S1. Add zinc acetate to a green tea extract to prepare nano-sheet zinc oxide; the preparation of the green tea extract includes removing impurities on the surface of the green tea leaves, washing and crushing the green tea leaves, adding ten times the weight of water and stirring at 70-80° C., filtering the filtrate using a non-woven filter material with an average pore size of 20-25 μm, and storing the filtrate at 4° C. for later use; S2, using 4-methylcyclohexanone solution and epoxy fatty acid methyl ester to modify poly (1,4-butylene adipate) to obtain modified poly (1,4-butylene adipate); S3, mixing high-density polyethylene and modified poly(1,4-butylene adipate) with nano-flaky zinc oxide, and extruding and granulating to obtain a cable sheath material.
2. The method for preparing the waterproof and corrosion-resistant cable sheath material according to claim 1, characterized in that: The preparation of the nano-sheet zinc oxide in S1 includes mixing a green tea extract with zinc acetate, stirring and reacting the mixture, cooling the mixture to room temperature, centrifuging the mixture to obtain a precipitate containing the nano-sheet zinc oxide, and drying and annealing the precipitate to obtain the nano-sheet zinc oxide.
3. The method for preparing the waterproof and corrosion-resistant cable sheath material according to claim 2, characterized in that: The mixing temperature is 60-80°C and the time is 1-2h; the centrifugal speed is 5000-7000rpm; the drying condition is 80-90°C and the time is 1.5-2.5h; the annealing condition is 190-210°C and the time is 2-3h; the mass ratio of the green tea extract to zinc acetate is 45-50:5-7.
4. The method for preparing the waterproof and corrosion-resistant cable sheath material according to claim 1, characterized in that: The preparation of the modified poly(1,4-butylene adipate) in S2 includes mixing 4-methylcyclohexanone solution, poly(1,4-butylene adipate) and epoxy fatty acid methyl ester for reflux reaction, then cooling to room temperature, adding excess ethanol, stirring and standing, filtering and drying to obtain a precipitate.
5. The method for preparing the waterproof and corrosion-resistant cable sheath material according to claim 4, characterized in that: The weight ratio of the 4-methylcyclohexanone solution, poly(1,4-butylene adipate) and epoxy fatty acid methyl ester is 100:4-6:8-12, and the mass ratio of the ethanol to poly(1,4-butylene adipate) is 4-6:400-450.
6. The method for preparing the waterproof and corrosion-resistant cable sheath material according to claim 4, characterized in that: The temperature of the reflux reaction in S2 is 70-80°C, and the reaction time is 20-24h; the stirring rate is 450-550r / min, and the stirring time is 1.5-2.5h; the standing time is 0.5-1h; and the drying is vacuum drying at 70-80°C for 3-4h.
7. The method for preparing the waterproof and corrosion-resistant cable sheath material according to claim 4, characterized in that: The filtration uses a vacuum filter, and the filtered solution is evaporated at a temperature of 50° C. and a vacuum degree of 0.1 bar. The obtained condensed solution is a 4-methylcyclohexanone solution, which can be stored and reused.
8. The method for preparing the waterproof and corrosion-resistant cable sheath material according to claim 1, characterized in that: The S3 comprises the following raw materials in parts by weight: 91-95 parts of high-density polyethylene, 4-6 parts of modified poly(1,4-butylene adipate), and 1-3 parts of nano-flaky zinc oxide; the extrusion granulation conditions are a temperature of 180-200° C. and a rotation speed of 300-380 r / min.
9. A sheath material obtained by the method for preparing a waterproof and corrosion-resistant sheath material for a cable as claimed in any one of claims 1 to 8.
Citation Information
Patent Citations
Waterproof chemical-corrosion-resistant heat tracing cable sheath material and preparation method thereof
CN104479191A
Compound-mixed tea polyphenol-rare-earth salt conversion liquid for magnesium alloy surface treatment and use method thereof
CN106399992A
Halogen-containing flame-retardant polyethylene sheath material
CN109111674A